Inhibitory synaptic plasticity - Woodin, Melanie A. (Springer, 2011)
Since its discovery and first publication in 1973, synaptic plasticity in its most popular form -- the plasticity of excitatory glutamatergic synapses -- has been widely investigated. But to fully understand how brain functions develop and are maintained, there is a need for studying the interaction between the different forms of plasticity. Inhibitory Synaptic Plasticity integrates studies that have examined the induction, expression and functional role of inhibitory synaptic plasticity at different organizational levels (from the neuron to the circuit), through four main parts: Refinement, Addiction, Pain & Injury, and Learning & Memory. This volume brings together a large portion of the current thinking about the plasticity of inhibitory synapses, and will foster new ideas and hypotheses for the study of brain circuits and their function.